Rhythmic cueing, dance, resistance training, and Parkinson's disease: A systematic review and meta-analysis - Karpodini, Claire Chrysanthi; Dinas, Petros C.; Angelopoulou, Efthalia; Wyon, Matthew A.; Haas, Aline Nogueira; Bougiesi, Maria; Papageorgiou, Sokratis G.; Koutedakis, Yiannis (Frontiers in Neurology, 2022)
Objectives The aim of the present systematic review and meta-analysis was to synthesize evidence associated with the functional and clinical effectiveness of rhythmic cueing, dance, or resistance training (RT) on motor and non-motor parameters in Parkinson's Disease patients, and to provide a comparative perspective not offered by existing systematic reviews. Methodology Eligibility criteria for selecting studies retained no restrictions in methodological design and included interventions of rhythmic cueing, dance, RT, and measurements of motor and non-motor parameters. Animal studies, reviews, editorials, conferences, magazines, and gray literature articles were excluded. Two independent investigators searched Cochrane Library, Medline, PubMed, and SPORTDiscus from the date of their inception until 1 June 2021. The ROBINS-I tool was employed for the non-randomized controlled trials, and the updated for Risk of Bias 2 tool of Cochrane Library used for randomized controlled trials. For meta-analyses, the RevMan 5.4.13 software was used. For incompatible meta-analysis studies, a narrative data synthesis was conducted. Results A total of 49 studies included in the systematic review involving 3767 PD participants. Meta-analyses revealed that rhythmic cueing training assists gait velocity (p = 0.01), stride length (p = 0.01), and motor symptoms (p = 0.03). Similarly, dance training benefits stride length (p = 0.05), lower extremity function-TUG (p = 0.01), and motor symptoms (p = 0.01), whilst RT improves lower extremity function-TUG (p = 0.01), quality of life (p = 0.01), knee flexion (p = 0.02), and leg press (p = 0.01). Subgroup analyses have shown non-significant differences in gait velocity (p = 0.26), stride length (p = 0.80), functional mobility-TUG (p = 0.74), motor symptoms-UPDRS-III (p = 0.46), and quality of life-PDQ39 (p = 0.44). Conclusion Rhythmic cueing, dance, or RT positively affect the examined outcomes, with rhythmic cueing to be associated with three outcomes (Gait, Stride, and UPDRS-III), dance with three outcomes (TUG, Stride, and UPDRS-III), and RT with two outcomes (TUG and PDQ-39). Subgroup analyses confirmed the beneficial effects of these forms of exercise. Clinicians should entertain the idea of more holistic exercise protocols aiming at improving PD manifestations. International Prospective Register of systematic reviews (PROSPERO) (registration number: CRD42020212380).